IMPLEMENTASI REPETITIVE METHOD MELALUI KEGIATAN REFLEKSI DALAM PEMBELAJARAN - Ester Caroline Wowor; Widya Anjelia Tumewu; Yohanes Bery Mokalu (LPPM Politeknik Saint Paul Sorong, 2022)
The development of the times demands an increase in the quality of human resources, including in the field of education. Students need to have a well-facilitated learning experience to make it easier to understand the material. Understanding learning materials can be made easier through reflection activities as a support for the repetitive method. Through reflection activities, students can recall the material and even the learning process that has been passed, so that the material will be more embedded in memory. The purpose of this study was to determine student responses to reflection activities. The research method used is a quantitative research method. The researcher used a questionnaire with a Likert scale rating as a research instrument. The data collection technique is in the form of a questionnaire technique. The researcher used purposive sampling technique and got 23 students who contracted the Educational Psychology course at the Science Education Department, Manado State University. The results showed that the students strongly agreed with the implementation of reflection activities in learning.